Efektivitas Terapi Relaksasi Autogenik pada Pasien Diabetes Mellitus Tipe 2 dengan Ketidakstabilan Kadar Glukosa Darah - Anggraini, Dian; Ubaidillah, Zaqqi (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Type 2 diabetes mellitus is a chronic disease characterized by hyperglycemia due to metabolic disorders related to insulin resistance and decreased pancreatic ?-cell secretion function. The high prevalence of DM, which continues to increase every year, indicates the need for comprehensive treatment to prevent complications. One non-pharmacological approach that can be used to help control blood glucose levels is autogenic relaxation therapy. This study used a case study design with a qualitative descriptive approach to explore in depth the phenomenon of changes in blood glucose levels in a patient with Type 2 DM. The research subject was one patient residing in Cokro Hamlet, Sukoanyar Village, with inclusion criteria including Type 2 DM patients, GDS >200, not consuming DM drugs or certain drugs, able to communicate, and willing to be a respondent. Primary data were obtained through interviews, observation of physical and psychological conditions, and blood glucose tests using a glucometer. Secondary data were obtained through patient health documentation, daily treatment records, and family statements. The research process was conducted in three stages, namely orientation, the working phase with the implementation of autogenic relaxation therapy in several sessions, and termination through subjective and objective evaluations. The results showed a decrease in blood glucose levels from 345 mg/dL to 216 mg/dL (a difference of 129 mg/dL) after the intervention, accompanied by improvements in physical and emotional complaints in the form of improved sleep quality, reduced fatigue, and decreased anxiety. These findings indicate that autogenic relaxation therapy can be an effective non-pharmacological intervention in helping to control blood glucose levels in patients with Type 2 DM.